MIGRATION-DEVELOPMENT-SECURITY NEXUS IN THE CONTEXT OF THE EXTERNAL DIMENSIONS OF THE EU POLICIES - Kübra Ergün; Ayşen Üstübici (Ankara Avrupa Çalışmaları Dergisi)
This paper questions how migration-development nexus has been conceptualized on the EU policymaking agenda since the early 2000s. To explore this question, this paper focuses on documents laying out Union’s strategy for the external dimensions of the EU migration policy. The empirical evidence is gathered from the content analysis of Council Conclusions, Commission’s Communications and Reports, and the secondary literature on external dimensions of the EU migration policy. Ourstudy finds that the already existing securitized approach to migrationdevelopment nexus prevailed after 2015, hollowing out the relation between migration and development with an increasingly narrower focus on development and the new narrative of ‘saving lives’. We conclude that the securitization of migration underpins the current ambivalent approach to the migration-development nexus in the EU policy-making context.